Prediction of lung tumor palpability using high-resolution computed tomography. (January 2016) - Isaka, Tetsuya; Ito, Hiroyuki; Yokose, Tomoyuki; Kondo, Tetsuro; Nagata, Masashi; Nishii, Teppei; Yamada, Kouzo; Nakayama, Haruhiko; Masuda, Munetaka
Background: Palpation is the most important means of locating lung tumors and resecting them with sufficient margins. This study aimed to predict the palpability of pulmonary lesions using high-resolution computed tomography. Methods: Eighty-six pulmonary lesions were palpated in fresh resected lung specimens from July 2013 to March 2014. The following parameters were compared between 10 impalpable and 76 palpable lesions: maximum tumor size in pulmonary and bone window level settings, consolidation tumor size in pulmonary window level setting, and pleural-tumor distance. In 54 adenocarcinomas, the lepidic component and fibrosis foci rates were compared between the two groups. Results: Tumor size in bone window level setting and the consolidation tumor size were significantly smaller in the impalpable group (both p < 0.001), and an operational cutoff of 5 mm was identified by receiver-operating characteristic analysis (sensitivity/specificity was 90.0%/94.7% and 90.0%/86.9%, respectively). Pulmonary lesions were impalpable with 87.5% probability when the tumor size in bone window level setting was ≤5 mm and the pleural-tumor distance was ≥ 5 mm, and with 85.7% probability when the consolidation tumor size was ≤5 mm and the pleural-tumor distance was ≥ 5 mm. Lepidic component and fibrosis foci rates of impalpable/palpable lesions were 96.0%/52.8% and 4.0%/24.7%, respectively (both p < 0.001). Conclusions: Tumor size in bone window level setting or a consolidation tumor size ≤5 mm and pleural-tumor distance ≥ 5 mm are simple criteria that are potentially useful indicators for preoperative marking to locate small-sized lepidic-predominant adenocarcinomas with few fibrotic foci.